A pathway to inclusive sustainable intensification in agriculture? Assessing evidence on the application of agroecology in Tanzania. Issue 2 (7th February 2019) - Mdee, Anna; Wostry, Alex; Coulson, Andrew; Maro, Janet
ABSTRACT: Neo-Malthusian narratives argue that the world urgently needs to produce more food for an expanding global population in the face of climate change, and that food security can only be assured through high input and large-scale agricultural production. This paper explores agroecology as an alternative approach to this narrative. Can a second "Green Revolution" be more "climate smart" and inclusive than the first one, through driving a process of genuinely sustainable intensification? Using a livelihoods framework, we assess evidence on the adoption of agroecological practices in the Uluguru Mountains in Tanzania, through a meta-analysis of four empirical studies, and conclude that the supported adoption of agroecological practice in conjunction with suitable market access has considerable potential for creating inclusive sustainable agricultural livelihoods.